Implementation of Law Number 18 of 2019 on Access to Education for Graduates of Muhammadiyah Boarding School Klaten at State Universities - Sandya Mahendra; Engine Kubota; Nabila Rahmawati Rama; M. Junaidi (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2021)
Islamic boarding schools are one of the educational programs among the many levels of education that have been passed down from generation to generation by the people of Indonesia. Islamic boarding school is a national education identity that has special characteristics in the form of religion-based education that is thick with scientific nuances. This study aims to 1) Know the definition of Islamic boarding school in law number 18 of 2019; 2) Knowing the implementation of Law No. 18 of 2019 on graduates of Islamic boarding schools in state universities. The research method used is normative legal research with a doctrinal approach with a descriptive type of study. Article 1 paragraph (1) of this Law states that Islamic boarding schools are community-based institutions established by individuals, foundations, Islamic community organizations, and/or communities that instill faith and piety to Allah SWT, cultivate noble character and adhere to the teachings of Islam. Islam rahmatan lil’alamin which is reflected in the attitude of humility, tolerance, balance, moderation, and other noble values of the Indonesian nation through education, Islamic da’wah, exemplary, and community empowerment within the framework of the Unitary State of the Republic of Indonesia. Muhammadiyah Boarding School Klaten or commonly referred to as MBS Klaten is a modern boarding school combining religious education with general science and Information Technology (ICT). The implementation of the law to accommodate graduates of Islamic boarding schools to continue their studies to a higher level has been carried out through a scholarship program to all Islamic boarding schools in Indonesia. However, MBS Klaten provides extremely strict requirements so that few students have the opportunity to continue their studies at State Universities.Keywords: Boarding school; Government policy; Education